Cerium conversion coating and sol-gel coating for corrosion protection of the WE43 Mg alloy. (September 2022) - Pereira, Gualter Silva; Prada Ramirez, Oscar Mauricio; Avila, Pedro Renato Tavares; Avila, Julian Arnaldo; Pinto, Haroldo Cavalcanti; Miyazaki, Marcos Hideki; de Melo, Hercílio Gomes; Bose Filho, Waldek Wladimir
Abstract: In this work, the electrochemical behavior and morphological characterization of a system consisting of a cerium conversion layer, a hybrid sol-gel coating, and the two coatings applied sequentially (duplex) have been evaluated for the corrosion protection of WE43 Mg alloy. The different characterization techniques showed that the surface coverage by the hybrid coating was improved by the previous application of the conversion coating. The fitting of the impedance diagrams with electrical equivalent circuits allowed to propose a physical model for the coating, evidencing its interaction with the porous Mg oxide/hydroxide layer. Self-healing properties of the duplex coating were also disclosed. Graphical Abstract: ga1 Highlights: CeP, Hyb and and duplex CeP-Hyb coatings is successfully prepared on WE43 alloy. The hybrid sol-gel coating improves corrosion protection of WE43 alloy in NaCl solution. The cerium conversion coating improves corrosion protection of WE43 alloy in NaCl solution. LEIM experiments showed self-healing capabilities for the CeP-Hyb sample.